If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9n + 12) = 0 Reorder the terms: (12 + 9n) = 0 Remove parenthesis around (12 + 9n) 12 + 9n = 0 Solving 12 + 9n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 9n = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 9n = 0 + -12 9n = 0 + -12 Combine like terms: 0 + -12 = -12 9n = -12 Divide each side by '9'. n = -1.333333333 Simplifying n = -1.333333333
| 100=t-48.3 | | (9n+12)=(15n-6) | | 12x-8=2x+2 | | 10y+15=5 | | 8b+2b^2=8 | | 10y+15=t | | X^2/x= | | -3(4x+5)=-27 | | 3(x-5)=5+(2x+3) | | 4x-3*7x-4=12 | | Y^*y^(3/4) | | F(x)=2+sin(2x+5) | | x^3-4=121 | | -4(1+7v)=20 | | 8x+3=3x-1 | | -32=-6+3(f-8) | | -28-4z=-6(8z-7) | | (x)(x)=(2x)(x-3)(.75) | | log(107-7x)=20th | | 0.1x-7=0.12x+14 | | Log(107-7x)=2 | | -28-4z=6(8z-7) | | 5y-14=21whatsy | | -32-(-58)= | | -5[v+9]=7v-21 | | Log(38-7x)=1 | | -5a+8+4a=21 | | 20x-12=10x+8 | | 3x+11=-2[x-3] | | 16/0.25 | | -4d-3-6=-17 | | 10-4y=5y |